2015
DOI: 10.1021/acs.joc.5b00891
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of 2-Alkoxyaryl-2-aryl Enamines via Tandem Copper-Catalyzed Cycloaddition and Rhodium-Catalyzed Alkoxyarylation from Alkynes, N-Sulfonyl Azides, and Aryl Ethers

Abstract: A synthetic route to a wide range of 2-alkoxyaryl-2-aryl enamines is developed from Rh-catalyzed alkoxyarylation of N-sulfonyl-4-aryl-1,2,3-triazoles with aryl ethers via the elimination of nitrogen molecule. In addition, 2-alkoxyaryl-2-aryl enamines are prepared via tandem Cu-catalyzed cycloaddition and Rh-catalyzed alkoxyarylation starting from alkynes, N-sulfonyl azides, and aryl ethers in one-pot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…N ‐Sulfonyl triazoles, precursors of azavinyl carbenes, are known to undergo a variety of rhodium‐catalyzed reactions. They have been used for the preparation of different types of heterocycles, N ‐sulfonyl‐containing compounds, and for stereoselective synthesis of 2,2‐diaryl or 2‐alkyl‐2‐aryl‐ substituted N ‐sulfonyl enamides (Figure B) . We have recently shown that N ‐fluoroalkyl triazoles prepared by a [3+2] cycloaddition of stable and safe azido(per)fluoroalkanes and alkynes are efficiently transformed to new N ‐fluoroalkyl heterocycles via rhodium carbenoids .…”
Section: Figuresupporting
confidence: 86%
See 1 more Smart Citation
“…N ‐Sulfonyl triazoles, precursors of azavinyl carbenes, are known to undergo a variety of rhodium‐catalyzed reactions. They have been used for the preparation of different types of heterocycles, N ‐sulfonyl‐containing compounds, and for stereoselective synthesis of 2,2‐diaryl or 2‐alkyl‐2‐aryl‐ substituted N ‐sulfonyl enamides (Figure B) . We have recently shown that N ‐fluoroalkyl triazoles prepared by a [3+2] cycloaddition of stable and safe azido(per)fluoroalkanes and alkynes are efficiently transformed to new N ‐fluoroalkyl heterocycles via rhodium carbenoids .…”
Section: Figuresupporting
confidence: 86%
“…They have been used for the preparation of different types of heterocycles, N-sulfonyl-containing compounds, [27] and for stereoselectives ynthesiso f2 ,2-diaryl or 2-alkyl-2-aryl-substituted N-sulfonyl enamides ( Figure 1B). [28][29][30][31][32][33] We have recently shown that N-fluoroalkyl triazoles prepared by a[ 3 + +2] cycloaddition of stable and safe azido(per)fluoroalkanes anda lkynes [34][35][36] are efficiently transformed to new N-fluoroalkyl heterocycles via rhodiumc arbenoids. [37,38] However,t he reactivity profiles of Nfluoroalkyl triazoles and N-sulfonyl triazoles are markedlyd ifferent.…”
mentioning
confidence: 99%
“…In the past few years, the use of readily accessible N -sulfonyl-1,2,3-triazoles 4 as a source of α-diazoimines has been greatly exploited in organic synthesis as a vital reactive intermediate. 5 Unlike traditional α-oxo metal carbenoids, metal carbenoids generated from α-diazoimines possess both an electrophilic carbon atom and nucleophilic nitrogen atom, which allows interesting inter/intramolecular reactions with various functional groups, like nitriles, 6 alkynes, 7 alkenes, 8 enol ethers 9 /enamines, 10 carbonyl compounds, 11 cumulenes, 12 C–H, 13 X–H 14 and C–X 15 bonds and other carbene induced transformations to functionalized carbo(hetero)cycles 16 and heteroatom-based building blocks. 17 Interestingly, 1,2-hydride or alkyl migrations onto the electrophilic carbenoid carbon of α-imino metalcarbenes were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 4‐phenyltriazole reacted with anisole ( 5 c ) and N , N ‐diethylaniline ( 5 d ) at 100 °C to afford the corresponding insertion products resulting from reactions at the para C(sp 2 )−H bonds. 4 a also gave the para ‐substituted products 9 and 10 when 5.0 equivalents of 5 c and 5 d , respectively, was used in 0.5 mL of chloroform at lower temperatures (conditions B) [Eqs.…”
Section: Figurementioning
confidence: 99%